Multiple extragastrointestinal stromal tumors: a case report - Alagarsamy, Jamila; Kadhirvel, Valarmathi; Kathirvel, Chandramouleeswari; Hemavathy, Arun; Lilly, Mary (International Journal of Advances in Medicine, 2017)
Gastro-Intestinal Stromal Tumor (GIST) is a non-epithelial, mesenchymal tumor. They most commonly originate from the stomach or small intestine, but in rare examples they involve the omentum in this article, we are reporting a case of multiple extragastrointestinal stromal tumour of the omentum, peritoneum and mesentery which was diagnosed cytologically and confirmed by histopathology and immunohistochemistry.